Optimizing Tumor Microenvironment for Cancer Immunotherapy: β-Glucan-Based Nanoparticles - Zhang, Mei; Kim, Julian A.; Huang, Alex Yee-Chen (Frontiers in Immunology, 2018)
Immunotherapy is revolutionizing cancer treatment. Recent clinical success with immune checkpoint inhibitors, chimeric antigen receptor T-cell therapy, and adoptive immune cellular therapies has generated excitement and new hopes for patients and investigators. However, clinically efficacious responses to cancer immunotherapy occur only in a minority of patients. One reason is the tumor microenvironment (TME), which potently inhibits the generation and delivery of optimal antitumor immune responses. As our understanding of TME continues to grow, strategies are being developed to change the TME towards one that augments the emergence of strong antitumor immunity. These strategies include eliminating tumor bulk to provoke the release of tumor antigens, using adjuvants to enhance antigen-presenting cell (APC) function, and employ agents that enhance immune cell effector activity. This article reviews the development of -glucan and -glucan-based nanoparticles as immune modulators of TME, as well as their potential benefit and future therapeutic applications. Cell-wall -glucans from natural sources including plant, fungi and bacteria are molecules that adopt pathogen-associated molecular pattern (PAMP) known to target specific receptors on immune cell subsets. Emerging data suggest that the TME can be actively manipulated by -glucans and their related nanoparticles. In this review, we discuss the mechanisms of conditioning TME using -glucan and -glucan-based nanoparticles, and how this strategy enables future design of optimal combination cancer immunotherapies.